Organizing KALAHI-CIDSS communities in Bugasong, Antique the experience of Barangay Bagtason and Barangay Igsoro. - Arnaiz, Elaine Grace P.
This undergraduate research entitled "Organizing KALAHI-CIDSS Communities in Bugasong, Antique: The experience of Barangay Bagtason and barangay Igsoro" is a documentation and analysis of the Community - Driven DEvelopment (CDD) approach to community organizing in the implementation of KALAHI-CIDSS Project in Barangay Bagtason and Barangay Igsoro in the municipality of Bugasong. The community organizing process, in the KALAHI-CIDSS CDD context, refers to the Community Empowerment Acitivity Cycle (CEAC) which serves as the framework for KALAHI-CIDSS Project implementation., Primarily through Focus Group Discussion (FGD) and Key Informant Interview (KII), the researchers were able to describe the organizing process that has transpired during the course of KALAHI-CIDSS Project implementation in the two barangays along with the challenges that they encountered. The data gathered from FGDs and KIIs were supplemented by the secondary data obtained from the KALAHI-CIDSS office in Bugasong such as Pariticipatory Situational Analysis (PSA) results, barangay profiles and other relevant records. The data collected from various sources were triangulated to come up with valid discussions, lessons, recommendations and analysis. Consolidation and analysis of the data is guided by the framework of the study and the people-centered development principles espoused by Manalili and Batistiana and Murphy.